2011
DOI: 10.1063/1.3546172
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pulse duration, energy, and focusing on laser-assisted water condensation

Abstract: We investigate the influence of laser parameters on laser-assisted watercondensation in the atmosphere. Pulse energy is the most critical parameter. Nanoparticle generation depends linearly on energy beyond the filamentation threshold. Shorter pulses are more efficient than longer ones with saturation at ∼1.5 ps. Multifilamenting beams appear more efficient than strongly focused ones in triggering the condensation and growth of submicronic particles, while polarization has a negligible influence on the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…However, due to several complications, including physical, chemical, and thermodynamic processes occurring in the propagation of femtosecond laser pulses in the cloud chamber, the water condensation induced by femtosecond laser filaments has not been fully understood yet. J.-P. Wolf and his collaborators proposed that the photo-oxidative chemistry of nitrogen induces the binary H 2 O-HNO 3 , which served as nucleation sites of water droplets [9,[18][19][20][21]. Our recent experimental results show that a continuous and intense updraft of warm moist air also played an important role in this process [22].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, due to several complications, including physical, chemical, and thermodynamic processes occurring in the propagation of femtosecond laser pulses in the cloud chamber, the water condensation induced by femtosecond laser filaments has not been fully understood yet. J.-P. Wolf and his collaborators proposed that the photo-oxidative chemistry of nitrogen induces the binary H 2 O-HNO 3 , which served as nucleation sites of water droplets [9,[18][19][20][21]. Our recent experimental results show that a continuous and intense updraft of warm moist air also played an important role in this process [22].…”
Section: Introductionmentioning
confidence: 63%
“…Because of its various applications, femtosecond laser filamentation has attracted lots of attention since several decades, including laser pulse self-compression [13], optical parametrical amplification [14], LIDAR (light detection and ranging) [10], remote sensing [8,15,16], and lightning control [17]. Recently, femtosecond laser-assisted water condensation as a candidate of rain making has been investigated both in a cloud chamber and the atmosphere [9,[18][19][20][21][22]. It is found that water condensation around the filaments can be triggered in both saturated and sub-saturated conditions [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the Thomson process1314, triggered by charges and typical of the Wilson chamber15, is irrelevant to the atmosphere because it requires supersaturation1617. Furthermore, we recently observed that laser-induced condensation and electron densities have different behaviours as a function of the incident laser power18.…”
mentioning
confidence: 99%
“…This laser-assisted water condensation was subsequently demonstrated in the atmosphere [12,13]. More recently, a laser-filamentation induced snow formation in a cloud chamber using high-repetition rate pulses has been reported [14].…”
mentioning
confidence: 97%